The Development of a Mathematical Adventure Game Using Construct2 Software - Mookkaew, Kasemphat; Kaewdee, Chatchai; Suwanrot, Thamasan (Academic Journal of Industrial Technology Innovation, 2024)
Games are crucial for digital-age learning in children and youth. This research aimed to develop a math adventure game using Construct2, a role-playing game (RPG), designed for primary school students in the first phase (Grades 1-3). The goal was to foster both learning and enjoyment while solving mathematical problems involving addition, subtraction, units, and tens. The expectation was that this would cultivate a positive attitude towards mathematics and enable students to use the game for reviewing lessons. The research employed the IMMCAI model, following a four-step process: (1) Analysis, (2) Design, (3) Development, and (4) Experimentation and evaluation. Three experts evaluated the game’s quality. The results indicated that the math adventure game developed using Construct2 was highly suitable for use as a teaching tool in primary school, specifically for Grades 1-3 ( = 3.97, S.D. = 0.56)